UTE’ SIMAGERE (TENGKORAK BAGI ROH): HUBUNGAN MASYARAKAT DENGAN PRIMATA ENDEMIK DI MENTAWAI - Tresno . (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2017)
Many think that the primate hunting is done by the Mentawai people caused the primate extinction in Mentawai whereas forest exploitation on Siberut Island has been going on for a long time like HPH, poaching, and development. Indeed, the Mentawai people have Arat Sabulungan guidance on their environment which not only regulate natural environment but the social and cultural environment. Based on the research of results found that the people of Buttui and Tepu’ know their world is divided into two parts, namely purimanuaijat (porak, manua, baga, oinan and leleu); and sabulungan (Saikamanua, Si Bara Ka Baga, Saikoinan and Saikaleleu). The world purimanuaijat in fact both the living things and inanimate objects have a soul (simagere) and spirit (ketsat). So the Mentawai people should maintain the relationship. Because human life that always utilize nature, can trigger the relationship, so they do punen and puliaijat. Because the balance is not only about the world purimanuaijat, but also the world sabulungan. So the Mentawai people perform the hunting activity at the end of the ceremony, due to the hunt for a form of respect for the spirits of the ancestors, Saikaleleu and fellow creatures who are spirited and have spirits by making ute 'simagere. The ethno-ecological Mentawai people have a categorization of the environment that are uma, pumonean consisting of pumonean saina and also pumonean leleu or siburuk; and leleu. Leleu this is a place of hunting and place of life for 4 species of endemic primates in the Mentawai. One of them are bilou, joja, simakobu and also bokkoi. As for the pumonean saina and pumonean leleu, it is advantageous to these four primates at the time of food to the four species of primates will descend to the fruit field as well as the bokkoi who can go down to the ground to take surappik. Likewise some taboos that save some primates while for the ceremony is not always the ending ceremony of hunting, so the ceremony and hunting are the mechanism of the Mentawai people in balancing the natural, social and cultural environment with a balance for the Mentawai people about the relationship between the world of purimanuaijat and the world of sabulungan.